High-frequency magnetic components - Kazimierczuk, Marian K., ....- (Chichester, U.K. : J. Wiley, 2009)
If you are looking for a complete study of the fundamental concepts in magnetic theory, read this book. No other textbook covers magnetic components of inductors and transformers for high-frequency applications in detail. This unique text examines design techniques of the major types of inductors and transformers used for a wide variety of high-frequency applications including switching-mode power supplies (SMPS) and resonant circuits. It describes skin effect and proximity effect in detail to provide you with a sound understanding of high-frequency phenomena. As well as this, you will discover thorough coverage on: integrated inductors and the self-capacitance of inductors and transformers, with expressions for self-capacitances in magnetic components; criteria for selecting the core material, as well as core shape and size, and an evaluation of soft ferromagnetic materials used for magnetic cores; winding resistance at high frequencies; expressions for winding and core power losses when non-sinusoidal inductor or transformer current waveforms contain harmonics. Case studies, practical design examples and procedures (using the area product method and the geometry coefficient method) are expertly combined with concept-orientated explanations and student-friendly analysis. Supplied at the end of each chapter are summaries of the key concepts, review questions, and problems, the answers to which are available in a separate solutions manual.
Fundamentals of magnetic devices -- Magnetic cores -- Skin effect -- Proximity effect -- Winding resistance at high frequencies -- Laminated cores -- Transformers -- Integrated inductors -- Self-capacitance -- Design of inductors -- Design of transformers.
Includes bibliographical references and index.
Keywords: Electromagnetic devices; Magnetic devices; Magnetisme